Improving poultry system in close house cage through advanced HVAC design: A Review of evaporative cooling pads and energy efficiency in broiler cages - Lillahulhaq, Zain; Widodo, Wawan Aries; Sutardi, Sutardi; Hakim, Luthfi; Nugroho, Anton (Mechanical Engineering for Society and Industry, 2024)
Improving the quality and quantity of livestock production can be achieved by creating a comfortable and safe environment for animals. The use of closed-house pens is one of the methods employed to control temperature, humidity, airflow, and the cleanliness of the living space for animals. Close-house pens are equipped with Heating, Ventilation, and Air Conditioning (HVAC), including the combination of an Evaporative Cooling Pad (ECP) and an exhaust fan. The characteristics of the shape and material composition of the ECP components influence pressure drop and the flow pattern entering the room. This research focuses on reviewing papers related to the development of numerical simulation studies of close-house pens and ECP. The design of numerical simulations and the selection of boundary conditions enhance the precision and error level of predicting fluid flow distribution in closed-house cages. In addition to numerical simulations, the application of energy management calculations provides recommendations regarding the combination of HVAC design and environmental control parameters that need to be considered.